Optimization of Ultrasound-assisted Extraction of Ulvan from Green Seaweed Ulva lactuca - Quang, Ngo Van; Anh, Nguyen Ngoc; Thu, Quach Thi Minh; Van, Tran Thi Thanh; Cuong, Dang Xuan; Tam, Nguyen Quang; Thuy, Thanh Thi Thu (VNU Journal of Science: Natural Sciences and Technology; Vol 38 No 3DO - 10.25073/2588-1140/vnunst.5371, 2022)
In this paper, the extraction conditions of ulvan from green seaweed Ulva lactuca by using Ultrasound-assisted extraction method were optimised. Experience was designed using Box-behnken model with experient areas as following: extraction temperature ( X 1 : 50–90 °C), extraction time ( X 2 : 20–40, min) and solvent-to-material ratio ( X 3 : 50/1–70/1, v/w), objective function ( Y : extraction yield) was required to get maximum value. The result showed that the optimization conditions for extraction were: extraction temperature 84.28 °C, extraction time 30.59 min with 60.21/1 (v/w) as solvent-to-material ratio, and the expected objective function Y is 22.86% based on dried seaweed weight.